HYPERTHYROIDISM SECONDARY TO GESTATIONAL TROPHOBLASTIC DISEASE : A LITERATURE REVIEW - Bagus Sentosa, I Gede (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Gestational trophoblastic disease (GTD) is a rare form of pregnancy-related cancer that is effectively treatable. GTD is accompanied by the potentially fatal complication of hyperthyroidism. We created a review consisting of five case reports. This case report was conducted on women who became pregnant when they were >35 years old. They showed consistent laboratory results, in which there was an increase in hCG levels. TSH and thyroid stimulating antibodies cannot account for the hyperthyroidism associated with GTD. The source of the thyroid stimulating agent is trophoblastic tissue. The thyrotropic effects of ?-hCG mediate GTD hyperthyroidism. Other research examined the prevalence of hyperthyroidism in women with normal pregnancy, hydatidiform mole, and choriocarcinoma who had ?-hCG serum levels below 100,000 IU/ml. Early prenatal screening may significantly reduce hyperthyroidism rates. Thyroid hormone synthesis inhibitors treat hyperthyroidism in pregnancy. Thioamides, propylthiouracil (PTU), and methimazole (MMI) are the most prevalent U.S. antithyroid medications (ATD). Plasmaphoresis may be an option for people who are resistant to therapy or need emergency surgery. GTD can cause fatal hyperthyroidism. Anti-thyroid medicines can handle most GTD hyperthyroidism. Surgery may be a possibility for patients refractory to medical treatment.